Desempenho de genótipos de feijão comum inoculados com estirpes de rizóbio associado à adubação nitrogenada - Reck, Sandra Aparecida Camacho (2014)
Studies with rhizobia strains with high symbiotic potential, previously selected and recommended strains for production of commercial inoculants in Brazil become of great importance to obtaining increases in nodulation, biological fixation of nitrogen and yield of common bean in tropical conditions. Thus, the present study aimed to evaluate the response of common beans subjected to inoculation with strains of Rhizobium sp. and nitrogen fertilization, analyzing aspects related to nodulation of plants and grain yield in three genotypes of crops in the rainy season 2012/2013, 2013/2014 and the dry season 2013. The experimental design was randomized blocks, in factorial scheme 5 x 3, with four replications, consisting of combinations of inoculation with UFLA 04-195 and UFLA 02-100 of Rhizobium etli strains, UFLA 02-127 of R. leguminosarum bv. phaseoli, SEMIA 4077 (CIAT 899 = BR 322) of R. tropici and without inoculation and nitrogen fertilization performed with three N rates (0.0, 40 and 80 kg ha-1). Inoculation of seeds was immediately before sowing with peat inoculant and nitrogen fertilization was performed using as source of N as urea, being divided doses at sowing and coverage (V4). The characteristics evaluated were: number of nodules, nodule dry weight, shoot dry mass, content and accumulation of nitrogen in shoots, number of pods per plant, number of grains per pod, weight of 100 grains and yield. Data were subjected to analysis of variance and means were compared by the Scott-Knott (1974) test for strains and Bonferroni test and regression doses. The common bean genotypes showed different responses, indicating that cultivars IPR Tangara and IPR Tuiuiu that have longer average cycle have greater potential to nodulation compared to IPR Eldorado. The cultivar IPR Tangara when inoculated with UFLA 04-195 and UFLA 02-127 strains had higher nodulation and grain yield. It was also found that the nitrogen fertilization adversely affect nodulation, but increasing doses of N increasingly influenced grain yield cultivars in two harvest IPR Tangara and IPR Tuiuiu - 2012/2013 harvest.